Giraffe skin disease: Clinicopathologic characterization of cutaneous filariasis in the critically endangered Nubian giraffe (Giraffa camelopardalis camelopardalis). Issue 3 (May 2022) - Han, Sushan; Dadone, Liza; Ferguson, Sara; Bapodra-Villaverde, Priya; Dennis, Patricia M.; Aruho, Robert; Sadar, Miranda J.; Fennessy, Julian; Driciru, Margaret; Muneza, Arthur B.; Brown, Michael B.; Johnston, Matthew; et al.
Giraffe skin disease (GSD) is an emerging disease of free-ranging giraffe recognized in the last 25 years in several species, including the critically endangered Nubian giraffe ( Giraffa camelopardalis camelopardalis ) of Uganda. Identifying the cause of GSD and understanding its impact on health were deemed paramount to supporting these vulnerable populations. Sixty-four giraffes were immobilized in Murchison Falls National Park, Uganda, from 2017 to 2019, and GSD lesions were opportunistically biopsied. Fifty-five giraffes (86%) had GSD lesions on the neck, axilla, chest, and cranial trunk. Lesions were categorized into early, intermediary, and dormant stages based on gross and histological characteristics. Early lesions were smaller, crusted nodules with eosinophilic and pyogranulomatous dermatitis and furunculosis. Intermediary lesions were thick plaques of proliferative and fissured hyperkeratosis and acanthosis with dense dermal granulation tissue and severe eosinophilic and granulomatous dermatitis. Lesions appeared to resolve to dormancy, with dormant lesions consisting of hairless plaques of hyperkeratosis with dermal scarring and residual inflammation. The periphery of early and intermediary lesions included follicular granulomas containing adult filarid nematodes, with myriad encysted microfilariae in the superficial dermis. Stage L3 larvae were common in early and intermediary lesions, and dormant lesions had remnant encysted microfilariae with no adult or stage L3 larvae. Nematodes were morphologically and genetically novel with close identity to Stephanofilaria spp. and Brugia malayi, which cause infectious filariasis. Identification of potential insect vectors, long-term monitoring of GSD lesions, and evaluating response to therapy is ongoing in the efforts to help conserve the Nubian giraffe.